Is Cardiology Evaluation Necessary in Children with Electrocardiogram Abnormalities Noted on Polysomnogram?. (3rd February 2014) - Baldassari, Cristina M.; Beydoun, Hind A.; Peak, Jessica; Reed, John H.
Abstract : Objectives: (1) To determine the prevalence of cardiac disease in children with electrocardiogram (ECG) abnormalities on polysomnogram (PSG). (2) To assess whether factors such as family history of heart disease and severity of sleep apnea are associated with cardiac disease. Study Design: Case series with chart review from 2002 to 2012. Setting: Tertiary children's hospital. Subjects and Methods: Children between 1 and 16 years of age with ECG abnormalities on PSG who were referred to cardiology for evaluation were included. Children with a known history of cardiac disease were excluded. Results: Sixty‐one children had ECG abnormalities on PSG and were subsequently referred to cardiology. The mean age was 6.5 years (SD, 4.5), and 64% (n = 39) of subjects were African American. The mean obstructive apnea hypopnea index (AHI) was 8.8 (SD, 13.3), and 26% of the children had severe obstructive sleep apnea (AHI >10). The most common ECG abnormality (n = 52) recorded on PSG was premature ventricular contractions. Thirty percent (n = 18) of children had marked arrhythmias noted on their PSG ECG. Most children referred to cardiology underwent echocardiogram (45/61) and 24‐hour arrhythmia monitoring (42/61). Five children (8%) had cardiac pathology, including atrial and ventricular ectopy, tuberous sclerosis, mitral regurgitation, and aortic insufficiency. Factors such as family history of heart disease ( P =. 40) and severe OSA ( P =. 74) were not associated with cardiac pathology. Conclusion: Cardiac pathology in children with abnormal ECGs on PSG is common. Cardiology referral in such patients should be considered. Further research is needed to determine the appropriate cardiac workup.